Sosialisasi Editorial Workflow dalam Mengoperasikan OJS 3 untuk Meraih Akreditasi SINTA Jurnal ISORI: Ikatan Sarjana Olahraga Kabupaten Kampar - Herli Pardilla; Jufrianis Jufrianis; Dedi Nofrizal; Muhammad Isnandar Muhammad Isnandar (Joska: Jurnal Isori Kampar, 2025)
Objectives: Strengthening editorial capacity is essential for improving the quality, credibility, and accreditation readiness of local scholarly journals. Many regional academic associations, including ISORI (Sports Graduates Association) Kampar Regency, still face challenges in operating Open Journal Systems (OJS) 3 and meeting national accreditation requirements such as SINTA. This community service program aimed to enhance the editorial competencies of ISORI Kampar Regency, particularly in mastering OJS 3 operations and aligning editorial practices with SINTA accreditation standards. Methods: A participatory and competency-based training approach was implemented through a series of workshops, hands-on practice sessions, and intensive mentoring over a three-month period. The program involved 25 editorial board members representing lecturers, sports teachers, coaches, and sports practitioners. Training components included needs assessment, theoretical instruction, practical workshops, simulation exercises, and continuous follow-up mentoring. Results: The program resulted in substantial improvements in participants’ editorial skills. Pre-test scores increased from 45.2% to 82.6% in the post-test evaluation. Participants demonstrated notable progress in OJS 3 basic operations (51% improvement), knowledge of SINTA accreditation standards (43% improvement), editorial management competencies (43% improvement), and troubleshooting skills (44% improvement). Additionally, 96% of participants reported high satisfaction with the program, and a functional editorial workflow was successfully established. Conclusion: This community service initiative effectively enhanced the editorial capacity of ISORI Kampar Regency and strengthened their readiness for SINTA accreditation. The improved competencies in manuscript management, peer review processes, and journal administration contribute significantly to elevating the quality of sports science publications and supporting the advancement of evidence-based sports research in Kampar Regency and the broader Indonesian academic landscape